The use of information operation activities in foreign electoral interference - Lassila, Siiri (2019)
This Bachelor’s Thesis is a literature review that is based mostly on scholarly articles and books and some military and governmental sources. Its purpose is first to explain what is information warfare and foreign electoral interference. It will be then shown how information warfare tactics can be used to intervene in the elections of a foreign nation via a case study of the US 2016 Presidential Election in which the Russian Government intervened. The thesis showed that the Russian government intervened in the election by an extensive social media disinformation campaign that involved the use of trolls, bots, disinformation, “active measures” and purchasing of political advertisements as well as computer network exploitation attacks on systems containing sensitive information and then the leaking of that information. These measures have also been used in other elections in Europe and can quite likely be used in future elections.